Optimized Double Manganese Oxide Deposition for Enhanced Electrochemical Capacitor Performance. Issue 8 (17th April 2020) - Allison, A.; Davis, M. A.; Licht, F.; Pratt, J. M.; Andreas, H. A.
Abstract : Manganese oxide pseudocapacitive materials are deposited using a novel procedure involving first depositing a heat-treated base layer followed by a hydrous top layer. The ratio of heat-treated to hydrous film is optimized to generate films that excel across a wide range of electrochemical capacitor (EC) properties and to elucidate the mechanisms underpinning the film performance. We show that a thin heat-treated base layer imparts low resistance, high energy efficiency and power-capability and enhanced film stability in a large potential window. These benefits are due to an improved oxide-current collector connection; however, if the layer is too thin (<25 nm), the stability is lost. Conversely, heat-treatment causes more parasitic oxidation reactions during initial film cycling, though these reactions are mitigated with a thick hydrous top layer. This hydrous film also affords high capacitance, capacity, coulombic efficiency and energy density due to an abundance of hydrated sites in the oxide to facilitate the cation insertion/removal needed for pseudocapacitance. The double-deposited films also show less self-discharge. We find that a dry:wet film ratio of 5:95 results in optimal film performance. While this novel dry-wet double-deposition has been demonstrated with manganese oxide, we anticipate similar performance benefits with other pseudocapacitive materials.